Foreign versus local investors: Who knows more? Who makes more? - Kalev, Petko S.; Nguyen, Anh H.; Oh, Natalie Y. (Journal of Banking & Finance, 2008)
This paper examines the nature of information asymmetry between foreign and local investors on the Helsinki stock exchange (HEX) for the period 1999–2004. We take into account the differences in informational characteristics by partitioning stocks into single-listed, cross-listed and internationally well-known stock categories, after which we compare foreign and local investors’ performance and trading advantages. Local investors have trading advantages in the short term in all stock categories. However, such local advantages diminish for Nokia, the only internationally well-known stock on HEX.